Decentralised H ∞ fuzzy filter for non‐linear large‐scale systems under imperfect premise matching. Issue 18 (1st December 2015) - Kim, Ho Jun; Park, Jin Bae; Joo, Young Hoon
Abstract : This study presents a decentralised H ∞ filter design problem for non‐linear large‐scale systems that are represented based on the Takagi–Sugeno fuzzy model. To enhance the design flexibility of the fuzzy filter for non‐linear large‐scale systems, the imperfect premise matching problem is adopted in the filter design procedure. In the sense of fuzzy Lyapunov, sufficient conditions for both asymptotic stability of the error system and a prescribed level of the H ∞ norm are ensured to guarantee the H ∞ fuzzy filter performance. The sufficient conditions are formulated in terms of linear matrix inequalities, which can be solved efficiently using convex optimisation algorithms. Finally, simulation examples are provided to verify the feasibility of the proposed approach.